Surface Analysis of Anodized Ti-45Nb Alloy - A. S. Oliveira; E. C. S. Barboza; M. A. Rocha; M. V. Silva; D. F. Rocha; I. S. Santos; S. Griza (Materials Research)
Titanium is extensively applied for dental implants manufacture due to its remarkable mechanical properties, corrosion behavior, and biocompatibility. To further improve these attributes, some TiNb alloys have been developed. This study investigates the Ti-45Nb alloy, aiming to optimize its biomechanical performance and osseointegration properties through micro-arc anodization. The research encompasses the analysis of the alloy's microstructure, surface modification via micro-arc anodization using H2SO4 solutions at concentrations of 1M, 1.5M, and 2M, characterization of surface properties, surface topography and roughness profiling, and surface energy analysis. The findings indicate that the micro-arc anodization treatment with 1.5M H2SO4 solution is the most effective to enhance biomechanical performance and osseointegration of the Ti-45Nb alloy.